First-void versus midstream urine culture for detection of Ureaplasma urealyticum in the urinary tract - Raddi, MSG; Lorencetti, N. C.; Rodrigues, S. A. (Soc Brasileira Microbiologia, 1995)
Quantitative Ureaplasma urealyticum culture was performed on clean first-void and midstream urine to evaluate the presence of these mollicutes in the urinary tract. The results, expressed as color changing units (CCU), showed that 14 (63%) of the 22 Ureaplasma urealyticum positive patients yielded counts equal to or higher that 10(7) CCU/mL for both the initial and the middle urine specimens. No abnormal chemical or microscopic findings (protein content, leukocyte numbers) were observed. The occurrence of U. urealyticum in midstream urine samples, even when numbers are considered, may be no more than a guide to the presence of ureaplasmas in the urinary tract.
Keywords: Ureaplasma urealyticum; urine culture; urinary tract infection